Deletion of Individual mRNA Capping Genes Is Unexpectedly Not Lethal to Candida albicans and Results in Modified mRNA Cap Structures - Dunyak, Donna S. (American Society for Microbiology, 2002)
Eukaryotic mRNAs are modified at the 5′ end with a cap structure. In fungal cells, the formation of the mRNA cap structure is catalyzed by three enzymes: triphosphatase, guanylyltransferase, and methyltransferase. Fungal capping enzymes have been proposed to be good antifungal targets because they differ significantly from their human counterparts and the genes encoding these enzymes are essential in Saccharomyces cerevisiae. In the present study, Candida albicans null mutants were constructed for both the mRNA triphosphatase-encoding gene (CET1) and the mRNA methyltransferase encoding gene (CCM1), proving that these genes are not essential in C. albicans. Heterozygous deletions were generated, but no null mutants were isolated for the guanylyltransferase-encoding gene (CGT1), indicating that this gene probably is essential in C. albicans. Whereas these results indicate that Cet1p and Ccm1p are not ideal molecular targets for development of anticandidal drugs, they do raise questions about the capping of mRNA and translation initiation in this fungus. Southern blot analysis of genomic DNA indicates that there are not redundant genes for CET1 and CCM1 and analysis of mRNA cap structures indicate there are not alternative pathways compensating for the function of CET1 or CCM1 in the null mutants. Instead, it appears that C. albicans can survive with modified mRNA cap structures.